Gut microbiome as a clinical tool in gastrointestinal disease management: are we there yet? - Quigley, Eamonn M. M. (Nature reviews. Gastroenterology & hepatology, 2017)
Gut microbiota research has rapidly evolved, but has yet to translate fully to the clinic. In this Perspectives, Eamonn Quigley explores whether the gut microbiota could be used as a clinical tool in gastrointestinal disease, providing a note of caution to the hype. Spurred on by ever-evolving developments in analytical methodology, the microbiome, and the gut microbiome in particular, has become the hot topic in biomedical research. Ingenious experiments in animal models have revealed the extent to which the gut microbiota sustains health and how its disruption might contribute to disease pathogenesis. Not surprisingly, associations between the microbiota and disease states in humans have been the subject of considerable interest and many links proposed. However, with rare exceptions, the incrimination of an altered microbiota in disease pathogenesis seems premature at this time given our incomplete understanding of the composition of the gut microbiota in health and the effect of many confounding factors in the interpretation of supposedly abnormal microbial signatures. Future studies must account for these variables and the bidirectionality of host–microorganism interactions in health and disease. In this Perspectives, the status of microbiota signatures in the clinical arena (for facilitating diagnosis or refining prognosis) will be critically assessed and guidance toward future progress provided.